The Christianization of Akpéma and Kondona Initiation Rites and Their Desecration by the Catholic Church in the Prefecture of Kozah in Northern Togo - TCHELEGUE, Nadiedjoh; TCHABLE, Boussanlegue; AMOUZOUVI, Dodji (PPSDP International Journal of Education, 2024)
The objective of this research is to examine the impact of the celebration of akpéma and kondona rites in church on their sacredness. The survey covered 80 people, including 25 catholic priests and 55 guarantors of Kabyè habits and customs, through to purposive sampling. Direct observation, individual interview and documentary research are the data collection techniques used. The data collected was subject to content analysis. The results indicate that upon entering the church, the akpéma and kondona rites were remodeled, losing everything that founded their sacredness: the eponymous ancestor, the sacred place, the mythical time, the founding myths, the bloody sacrifices, the person of the celebrant (cojo) and his verbal words. However, some new landmarks allow us to note an attempt at their resacralization by the church.